Pemantauan Status Gizi Balita Di Desa Saronda Kecamatan Bajo Barat: Pemantauan Status Gizi Balita Di Desa Saronda Kecamatan Bajo Barat - Fitriana Ibrahim; Sumarni Sumarni; Ajeng Anggreny Ibrahim Ajeng (JCS, 2023)
Toddlerhood is the most important period in the life cycle, at the age of 0 to 5 years toddlers experience physical, mental and behavioral development. Nutritional status is the condition of the body as a result of consuming food and using nutrients, where nutrients are needed by the body as a source of energy, growth and maintenance of body tissues, as well as regulating body processes. This research was conducted to determine the factors related to the nutritional status of toddlers in Saronda Village, West Bajo District in 2022. The type of research used was analytic descriptive research with a cross-sectional approach. The sample in this study amounted to 53 respondents. The analysis of this study used the chi square test. The results of the bivariate analysis showed that there was an effect of economic status on the nutritional status of toddlers in Saronda Village according to the Chi Square test with a value of p = 0.000 (<0.05). And there is no effect of Mother's Knowledge on the Nutritional Status of Toddlers in Saronda Village according to the Chi Square test with p = 0.215 (> 0.05). There is an effect of economic status on the nutritional status of toddlers in Saronda Village according to the Chi Square test with a value of p = 0.000 (<0.05). And there is no effect of Mother's Knowledge on the Nutritional Status of Toddlers in Saronda Village according to the Chi Square test with p = 0.215 (> 0.05).